Review of Fiqh and Statutory Law Concerning Wakaf Land Exchange Affected in the Semarang - Demak Toll Road Project - Baehaqi, Ja'far; Khoirin, Nur (Walisongo Law Review (Walrev), 2022)
Replacement of waqf land is a problematic issue. This study aims to find answers to problems regarding mechanisms and procedures for replacing waqf land affected by the Semarang-Demak Toll Road project as well as an analysis from the point of view of fiqh and law. With research on normative law/doctrinal law as optical and field data as a basis for analysis, this research finds that the many stages taken and the involvement of many parties in the process of replacing waqf land is an effort and legal engineering to guarantee benefit, both in the form of immortality of waqf land and designation. Engineering carried out is an act/action that is not prohibited according to sharia. Therefore, engineering to replace waqf land is permissible and legal. Legal engineering, as stated in various laws and regulations, is a manifestation of functional legal instrumentation. Various laws and regulations, especially the Waqf Law and its implementing regulations have become a means of achieving development goals. In fact, the Waqf Law, unlike other laws and regulations, is able to penetrate so deeply in reaching theological matters. This is reasonable because the Waqf Law is nothing but the result of the positivization of Islamic law/fiqhPenggantian tanah wakaf merupakan masalah yang problematik. Penelitian ini bertujuan untuk menemukan jawaban atas permasalahan mengenai mekanisme dan prosedur penggantian tanah wakaf yang terkena proyek Jalan Tol Semarang-Demak serta analisis dari sudut pandang fikih dan hukum. Dengan penelitian terhadap hukum normatif/doktrin hukum sebagai optik dan data lapangan sebagai dasar analisis, penelitian ini menemukan bahwa banyaknya tahapan yang ditempuh dan keterlibatan banyak pihak dalam proses penggantian tanah wakaf merupakan upaya dan rekayasa hukum untuk menjamin kemanfaatan, baik berupa keabadian tanah wakaf maupun peruntukannya. Rekayasa yang dilakukan merupakan perbuatan/perbuatan yang tidak dilarang menurut syariah. Oleh karena itu, rekayasa untuk menggantikan tanah wakaf diperbolehkan dan sah. Rekayasa hukum, sebagaimana tertuang dalam berbagai peraturan perundang-undangan, merupakan perwujudan dari instrumentasi hukum fungsional. Berbagai peraturan perundang-undangan, khususnya UU Wakaf dan peraturan pelaksanaannya telah menjadi sarana pencapaian tujuan pembangunan. Padahal, UU Wakaf, tidak seperti peraturan perundang-undangan lainnya, mampu menembus begitu dalam hingga menyentuh persoalan teologis. Hal ini wajar karena UU Wakaf tidak lain merupakan hasil positivisasi hukum/fiqh Islam.